2006
DOI: 10.1029/2005jd006116
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Atmospheric Infrared Sounder temperature and water vapor retrievals with matched radiosonde measurements and forecasts

Abstract: [1] An evaluation of the temperature and moisture profile retrievals from the Atmospheric Infrared Sounder (AIRS) data is performed using more than 2 years of collocated data sets. The Aqua-AIRS retrievals, global radiosonde (RAOB) measurements, forecast data from the National Center for Environmental Prediction Global Forecasting System (NCEP_GFS), the European Center for Medium Range Forecast (ECMWF), and the operational retrievals from the NOAA 16 satellite Advanced TIROS Operational Vertical Sounder (ATOVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
302
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 316 publications
(334 citation statements)
references
References 20 publications
26
302
0
6
Order By: Relevance
“…These atmospheric profiles were retrieved from cloud-cleared AIRS radiances within each AMSU footprint. Validations with radiosonde data from the NOAA-NESDIS operational meteorological database archive (Divakarla et al, 2006) and with Atmospheric Radiation Measurement (ARM) data (Tobin et al, 2006) have shown that the accuracy is close to 1 K in 1 km layers for temperature and better than 15% in 2 km layers for water vapour. For the cloud property retrieval we have collocated the AIRS L2 standard products (version 5) with a subset of AIRS L1B radiance measurements which have been downloaded from the NASA data pool (http://mirador.gsfc.nasa.gov).…”
Section: Airs Datamentioning
confidence: 99%
“…These atmospheric profiles were retrieved from cloud-cleared AIRS radiances within each AMSU footprint. Validations with radiosonde data from the NOAA-NESDIS operational meteorological database archive (Divakarla et al, 2006) and with Atmospheric Radiation Measurement (ARM) data (Tobin et al, 2006) have shown that the accuracy is close to 1 K in 1 km layers for temperature and better than 15% in 2 km layers for water vapour. For the cloud property retrieval we have collocated the AIRS L2 standard products (version 5) with a subset of AIRS L1B radiance measurements which have been downloaded from the NASA data pool (http://mirador.gsfc.nasa.gov).…”
Section: Airs Datamentioning
confidence: 99%
“…The clearest field of view in the 3 × 3 block is selected, and a single cloud-cleared infrared spectrum for the block is computed (Cho and Staelin, 2006). Validation of AIRS operational retrievals for the troposphere provide an accuracy which is near the anticipated absolute accuracy of 1 K root mean square over a 1 km layer Divakarla et al, 2006;. A root mean square deviation of 1.2 and 1.7 K is found in the troposphere and lower stratosphere, respectively, by comparing AIRS with radiosondes .…”
Section: Airs and Hirdls Observations And Temperature Retrievalsmentioning
confidence: 99%
“…Reanalysis data sets include the European Centre for Medium-Range Weather Forecasts (ECMWF) ERA-Interim product (Dee et al, 2011), the National Centers for Environmental Prediction (NCEP; Kalnay et al, 1996) product, the Arctic System Reanalysis (ASR; Bromwich et al, 2010), and the Japanese 55 year Reanalysis (JRA-55; Kobayashi et al, 2015). Satellite products included were the Atmospheric Infrared Sounder (AIRS) Divakarla et al, 2006), Microwave Integrated Retrieval System (MIRS) (Boukabara et al, 2010), MH08 retrieval, and PLDC16 retrieval. AIRS satellite data included three different products: infrared measurements, microwave measurements (using AMSU-A), and combined (infrared and microwave) measurements.…”
Section: Assessment Of Water Vapour Column Using Gvrmentioning
confidence: 99%